ANALISIS KEBUTUHAN DAN DESAIN E-BOOK INTERAKTIF BERBASIS KONTEKSTUAL PADA MATERI BANGUN DATAR - Rahmy Idris; Usman Mulbar (PHI: Jurnal Pendidikan Matematika, 2026)
The low level of students’ conceptual understanding in plane geometry is caused by learning practices that are still oriented toward memorizing formulas, thus requiring innovative learning media that can support meaningful understanding. This study aims to analyze the needs and design a contextual-based interactive e-book for plane geometry material for eighth-grade students in junior high school. This research employs a conceptual design approach using the Research and Development (R&D) method, limited to the stages of needs analysis and product design. Data were obtained through a literature review related to digital learning media, interactive e-books, and contextual approaches, and were analyzed using descriptive qualitative techniques. The results indicate that the interactive e-book is designed with a systematic structure, including concept maps, gradual material presentation, and the integration of interactive features such as animations, videos, and exercises. The contextual approach embedded in the e-book enables students to understand mathematical concepts through their connection to real-life situations. Therefore, the contextual-based interactive e-book contributes as a potential learning medium to improve students’ conceptual understanding and to support more active, interactive, and independent learning.